Update on Cuticular Wax Biosynthesis and Its Roles in Plant Disease Resistance - Wang, Xiaoyu (Int J Mol Sci, 2020)
The aerial surface of higher plants is covered by a hydrophobic layer of cuticular waxes to protect plant tissues against enormous environmental challenges including the infection of various pathogens. As the first contact site between plants and pathogens, the layer of cuticular waxes could function as a plant physical barrier that limits the entry of pathogens, acts as a reservoir of signals to trigger plant defense responses, and even gives cues exploited by pathogens to initiate their infection processes. Past decades have seen unprecedented proceedings in understanding the molecular mechanisms underlying the biosynthesis of plant cuticular waxes and their functions regulating plant–pathogen interactions. In this review, we summarized the recent progress in the molecular biology of cuticular wax biosynthesis and highlighted its multiple roles in plant disease resistance against bacterial, fungal, and insect pathogens.